2009
DOI: 10.1002/ajmg.a.33077
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of patients with Niemann‐Pick disease, type B

Abstract: Health-care providers have only begun to understand the medical aspects of Niemann-Pick disease type B (NPDB), a relatively rare disease. Even less information is known about the psychological effects of living with NPDB. Patients with NPDB and their families face numerous psychological stressors including extensive medical testing, uncertainty of diagnosis, living and coping with a chronic illness, and grief and bereavement surrounding this progressively debilitating, and, ultimately, fatal disease. We used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 18 publications
2
34
1
1
Order By: Relevance
“…Previous research in this area has identified parents’ use of a range of strategies that included proactive coping, other positive coping strategies (e.g., religion, emotional/social support), and less adaptive means of coping (such as substance use) [24]. Similar to our study, others have identified social support, including close family and friend relationships [5, 20, 25, 26] and social media [27], as important to caregiver and family well-being. These informal support systems were commonly identified as important in our study, while the receipt of formal psychological or counselling services was mentioned less frequently by participants.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous research in this area has identified parents’ use of a range of strategies that included proactive coping, other positive coping strategies (e.g., religion, emotional/social support), and less adaptive means of coping (such as substance use) [24]. Similar to our study, others have identified social support, including close family and friend relationships [5, 20, 25, 26] and social media [27], as important to caregiver and family well-being. These informal support systems were commonly identified as important in our study, while the receipt of formal psychological or counselling services was mentioned less frequently by participants.…”
Section: Discussionsupporting
confidence: 78%
“…Families’ concerns about the social development of children with IMD may be exacerbated during life transitions, particularly adolescence [25, 27], and may be more prevalent for IMD characterized by significant physical disability [25]. In our study we identified social challenges in families of relatively young children (up to age 7) that were mainly connected to the need for specialized diets, and thus we were unable to corroborate previous research about transitions to adolescence and adulthood.…”
Section: Discussioncontrasting
confidence: 65%
“…Yet, frustration is not an issue experienced only by those without a diagnosis. Other studies have shown that frustration also occurs when parents do have a diagnosis (Russ et al, 2004;Wennick and Hallstrom, 2007;Doig et al, 2009;Henderson et al, 2009). Further, a number of other findings from this study, including the reasons given for wanting a diagnosis, the active role that parents play in managing care and treatment for their child, and the maternal difficulties in meeting employment expectations, were experienced in other studies in which the child did have a diagnosis (Young et al, 2002;Hummelinck and Pollock, 2006;Green, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Items in this domain along with questions about relationships with family and peers, are based in part on the work of Mellin and her colleagues (Mellin et al 2004) in their study of parents' experiences of parenting an adolescent daughter with type 1 diabetes. In addition, these questions were drawn from semi-structured interviews used to examine the experiences of patients with other inherited metabolic disorders including Neimann Pick B (NPD type B) (Henderson et al 2009) Gaucher disease (Packman et al 2006) as well as from surveys from parents of children with MSUD (Packman et al 2007).…”
Section: Semi-structured Interviewsmentioning
confidence: 99%